Coaching: leadership and professional development - Ortiz Luzuriaga, Daniel Hernán; Alvarez Maldonado, Johanna Andrea; Coronel Perez, Iván Ariolfo; Acosta Véliz, Marjorie Marcela (Revista Universidad de Guayaquil, 2020)
Objective: To analyze the coaching as a tool for business learning and development. Materials andmethods: this research is a qualitative literature review which describes the application of coachingin business and presents results of success in practical cases. Results: Optimizing the qualities andbusiness skills is a key factor for the achievement of targets and development of organizations.Business coaching is a tool that encourages the human resource, promoting actions change,involvement in the decision making and leadership evident in performance improvement.Conclusions: Coaching influence in the management of human talent improving performance andwork climate. It is a creative and stimulating process that serves as inspiration to maximize theirpersonal potential
Keywords: Business Coaching; Motivation; Business Training; Leadership